DESIGN OF SUPPLY CHAIN STRATEGY AS A TOOL FOR THE DEVELOPMENT OF THE COUNTRY'S ECONOMY - Nasimiqizi Gasimova, Elfana; Afonasova, M. A.; Kuprina, A. V.; Abramov, V. L. (International Journal of Supply Chain Management, 2020)
Abstract- Modern society has entered the stage of its development when the objective world around us, created by supply chai nstrategies, is experiencing a period of rapid growth. More and more complex are filling market niches. The requirements for consumer properties of products are becoming ever higher. Today it is already obvious that only collective creativity can ensure high competitiveness of products. Today, design is a strategic tool, the correct use of which leads to success in business. The relevance of the study is caused by a very low level of research on the development aspect of the country's economy ? supply chain design.